Development of an Integrated Physics Problem-Solving Model in Virtual Media for Class XI Students - Astuti, Wahyu Indah Widya; Hermansyah, Hermansyah; Fitriyanto, Syarif; Yahya, Fahmi; Nisyah, Mir'atun (Faculty of Science and Education, UIN Walisongo Semarang, 2025)
This research and development aims to determine the feasibility of developing problem-solving-based learning tools assisted by virtual media. The type of research used is Research and Development (R&D) with the ADDIE model (analysis, design, development, implement, evaluate), which is only carried out up to the development stage. The subjects of this research were physics teachers and students of class XI IA MAN 1 Sumbawa for the 2022/2023 academic year. The research instrument uses a questionnaire for material experts, media, practitioners, and students. The instruments used were validation questionnaire sheets and student response questionnaires to determine the feasibility of problem-solving-based learning tools assisted by virtual media. Based on the results of expert validation and product trials, it shows that the product quality has reached the appropriate standards for learning media. Material expert validation obtained an average percentage result of 96.67% with the criteria